1994
DOI: 10.2307/2445401
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Viability, Vigor, and Competitive Ability in Erythronium grandiflorum (Liliaceae)

Abstract: To determine how the capability of pollen is affected by lengthy exposure to field conditions, we obtained pollen samples (from Erythronium grandiflorumi that were fresh (from newly dehisced anthers) or aged, from 6 to 24 hr. Without pretreating the collected grains, we compared their abilities I) to retain viability, as indicated by the Heslop-Harrison fluorochromatic reaction (FCR) test; 2) to retain germinability, as indicated by pollen-tube growth in vitro on Brewbaker-Kwack medium; 3) to sire seeds when u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
1
17
0
1
Order By: Relevance
“…Therefore, the simultaneous use of several tests should be supported in order to evaluate the different features of pollen viability (Dafni and Firmage, 2000;Rodriguez-Riano and Dafni, 2000;Thomson et al, 1994). New applications of microfluidic impedancebased flow cytometry (Cheung et al, 2010;David et al, 2012) are highly promising for the evaluation of pollen viability and have to be considered also for direct applications in agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the simultaneous use of several tests should be supported in order to evaluate the different features of pollen viability (Dafni and Firmage, 2000;Rodriguez-Riano and Dafni, 2000;Thomson et al, 1994). New applications of microfluidic impedancebased flow cytometry (Cheung et al, 2010;David et al, 2012) are highly promising for the evaluation of pollen viability and have to be considered also for direct applications in agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…Snow cover on the control plots may provide better insulation from low night-time temperatures compared with any extra warmth the heaters may have provided. Although foliar tissues of E. grandiflorum recover rapidly following freezing (Germino & Smith, 2001; but see Loik et al, 2004), floral tissues appear quite sensitive to temperature (Thomson et al, 1994;Price & Waser, 1998). Loewen et al (2001) found that populations of E. grandiflorum at highelevation sites in British Columbia produced proportionately fewer flowers than low-elevation populations.…”
Section: Reproductive Effortmentioning
confidence: 99%
“…Bjo$ rkman et al, 1995 ;Snow & Spira, 1996) provide evidence for non-random fertilization, the association between pollen tube growth and seed-siring success has not been straightforward (Melser et al, 1997 ; J. I. Hormaza & M. Herrero, unpublished ; see also Thomson et al, 1994). Melser et al (1997) found that the parental combinations that sired relatively many seeds did not have high pollen-tube growth rates in Echium vulgare.…”
Section: mentioning
confidence: 99%